Gynesis in selected short fiction in English by Filipino women writers - Negado, Christine Odette M. (Animo Repository, 1998)
This thesis, Gynesis in Selected Short Fiction in English by Filipino Women Writers applies Alice Jardine's concept of gynesis in the analysis of 23 selected works of short fiction in English written by Filipino women. The study determines whether or not the Filipino woman is transformed into a speaking subject within the narratives. It also determines whether or not the Filipino woman has been put into the discourse. Important to the study are several of the women's anthologies published from the 1980's to the present. These anthologies are the sources of the works of short fiction in English used in the study. Gynesis is the framework of the study because there have been little or no developments in this field of feminism here in the Philippines. This concept involves the analysis of the discourse of fiction in order to arrive at other truths . In venturing into other truths , the feminine or woman is made present in the discourse. The analyses of the selected works of short fiction in English reveals that the Filipino woman is transformed into a speaking subject within the narrative. Through the use of the narrative voice, the female protagonist character acts, speaks, creates, thinks, passes judgments and arrives at realizations concerning herself and her life (or is allowed to do so). The feminine or woman has also been made present in the discourse of the selected texts. Most of these selected texts venture into alterity through the requestioning and rethinking of several long-held master narratives and concepts about God, Christianity, man, womanhood, sex, space and time. In doing so, there is the incorporation of mysticism, sensuality, sexuality and sacredness in these texts in the attempt to veer away from the traditional and conventional truths or narratives. It is the aim of the study to contribute to feminist criticism in the Philippines, specifically in the field of gynesis.